PENGARUH PEMBIAYAAN MUDHARABAH, MUSYARAKAH, MURABAHAH DAN IJARAH TERHADAP PROFITABILITAS BANK UMUM SYARIAH (BUS) YANG TERDAFTAR DI OTORITAS JASA KEUANGAN (OJK) - Abdul Hadi Sirat (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2018)
This study aims to determine the effect of Mudharabah, Musyarakah, Murabahah and Ijarah on Profitability partially and simultaneously on Islamic Commercial Banks (BUS) registered with the Financial Services Authority (OJK). The research period used is 5 (five) years, namely 2012-2016. The data is in the form of financial statements of Sharia Commercial Banks (BUS) in Indonesia in 2012-2016. The data source used is secondary data. The population used in the study is the Islamic Commercial Bank (BUS) registered with the Financial Services Authority (OJK) for the period 2012-2016. The sample was determined by purposive sampling method and obtained 11 Islamic Commercial Banks (BUS). The analysis used in this study is multiple linear regression. The results of data analysis, mudharabah financing has no effect on profitability. Musyarakah financing influences profitability. Murabahah financing affects profitability and Ijarah Financing has no effect on profitability. Simultaneously mudharabah, musyarakah, murabahah and ijarah financing affect profitability.